Miscoordination Reduction of Directional Overcurrent Relay by Memetic Algorithm - ทิพจร, วิวัฒน์ (Srinakharinwirot University Engineering Journal, 2018)
This paper presents coordination of directional overcurrent relays by optimization technic using memetic algorithm, combined with genetic algorithm and shuffled frog leaping algorithm. In addition, this paper proposes a new unconstrained objective equation to reduce miscoordination of main and backup relays, considered near and far-end faults. The proposed method is implemented in two different test cases, three and six bus network. The results show that, in the case of the 3 bus system, the discrimination times are decreased. And in the case of the 6-bus system, the proposed objective equation can reduce miscoordination, at the far-end fault, from 8 points to 2 points. It is found that the effectiveness and superiority of the memetic algorithms compared with the performance of genetic and shuffled frog leaping algorithm.